Hepatorenal Syndrome: Examine the Treatment Effectiveness of Terlipressin and Albumin - Zafar Ahmad Khan, Muzamul Shahzad, Javed Iqbal, Muhammad Imran Aslam, Altaf Ahmad Yar, Munaza Javed, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find the efficacy of albumin and terlipressin in the management of hepatorenal syndrome. Study Design: Randomized control trial. Place and Duration Study: Department of Medicine, Bolan University of Medical & Health Sciences, Quetta from 1st March 2020 to 30th September 2020. Methodology: Eighty four patients of both the genders were enrolled. Complete demographic details regarding age, sex, gender, weight and height was noted. Study participants were divided into two groups; patients of group A received terlipressin with albumin whereas patients of group B only received albumin. Comparative results were obtained and effectiveness examined for 15 days. Results: Mean age of group A participants was42.38±8.46 years and there were 28% males and 62% female. Whereas in Group B, mean age of study participants was41.27±9.51 years and there were 54% males and 45% females. Similarly, mean BMI of group A and group B patients were 23.24±2.18kg/m2 and 22.18±2.24 kg/m2respectively. Almost 78% efficacy was observed in group A while only 47% was observed in group B. Conclusion: Higher effectiveness with terlipressin with albumin was observed in contrast to albumin alone. Keywords: Terlipressin, Efficacy, Albumin, Hepatorenal syndrome